Antithymocyte globulin is associated with a lower incidence of de novo donor‐specific antibody detection in lung transplant recipients: A single‐center experience - Tathagat Narula; Samir Khouzam; Francisco Alvarez; David Erasmus; Zhuo Li; Yousif Abdelmoneim; Mohamed Elrefaei (Immunity, Inflammation and Disease, 2021)
Abstract Purpose Induction immunosuppression has improved the long‐term outcomes after lung transplant. This is the first report exploring the association of induction immunosuppression with the development of de novo donor‐specific human leukocyte antigen (HLA) antibodies (DSA) in lung transplant recipients (LTR). Methods Sixty‐seven consecutive primary LTR were followed for 3 years posttransplant. A total of 41/67 (61%) LTR‐received induction immunosuppression using a single dose of rabbit Antithymocyte Globulin (rATG; 1.5 mg/kg) within 24 h of transplant. All recipients had a negative flow cytometry crossmatch on the day of transplant. Serum samples at 1, 3, 6, and 12 months posttransplant were assessed for the presence of de novo HLA DSA. Results De novo HLA DSA were detected in 22/67 (32.8%) LTR within 1‐year posttransplant. Of these, 9/41 (21.9%) occurred in the induction therapy group and 13/26 (50%) in the noninduction group. Class II DSA were detected in 3/41 (7.3%) LTR who received induction compared to 9/26 (34.6%) LTR without induction immunosuppression (p = .005). Differences in overall survival or freedom from chronic lung allograft dysfunction rates between the two groups were not statistically significant. Conclusion Induction immunosuppression utilizing a modified regimen of single‐dose rATG is associated with a significant reduction in de novo DSA production in LTR.